Evaluation efficacy and safety of epidural analgesia in second-trimester induced labor: A single-center, prospective, non-randomized, controlled study. Issue 38 (23rd September 2022) - Zeng, Yong; Jiang, Tao; Zheng, Ya-Hong; He, Wen-Rong; Wang, Xiao-Wen; Wei, Hua; Wang, Li; Liu, Zu-Rong; Zhang, Xu-Feng; Yi, Cunjian; Chen, Ke-Ming
Abstract : Background: Second-trimester induced labor in pregnant women was often more likely to suffer from psychological and physiological double pain. However, the analgesic management received less attention, and the optimal analgesic mode for second-trimester induced labor had not been determined. Our objective was to evaluate the feasible of epidural analgesia (EA) in second-trimester induced labor. Methods: From January 2020 to December 2021, Primipara who planned to undergo second-trimester induced labor in the First Affiliated Hospital of Yangtze University were collected. The method of labor induction was oral mifepristone + amniotic cavity injection of Ethacridine Lactate. Based on whether or not patients received epidural analgesia, which were divided into EA group (30 cases) and non-EA (NEA) group (30 cases). The primary outcome were visual analog scale (VAS) score of pain and result of follow-up, the secondary outcomes included relative clinical parameter and labor duration. Results: Vaginal induction of labor was successful in both groups. There was no statistically significant difference in VAS of pain between the two groups before analgesia ( P > .05), but the VAS of pain in the EA group was significantly lower than the NEA group ( P < .05) after analgesia or at delivery. The following outcomes showed no statistical difference between two groups: labor duration, postpartum hemorrhage, hemorrhage ≥ 500 mL, intrapartum injury, second days hemoglobin, C-reactive protein, antibiotic therapy days, hospitalizations days, and placenta residue ( P > .05). The median hospitalization costs of EA group was 4697.5 yuan, and NEA group was 3673 yuan, the difference was statistically significant ( P < .001). No adverse events related to EA occurred during hospitalization, only 3 patients showed mild lumbago and back pain after follow-up to three months postpartum, which was significantly relieved after proper rest. Conclusion: EA can significantly reduce the pain of parturients, which may be effective and safe in the second-trimester induced labor.